Lung Cancer Patient Description in Immanuel Hospital Bandung from January 2013 to December 2014 - Ida AKT Bulan; Hana Ratnawati; Teresa L Wargasetia (Journal of Medicine and Health, 2017)
Lung cancer is a disease which has high incidence and mortality rate. It makes lung cancer become one of the biggest public health problems. The aim of this study is to find out the description of lung cancer patients in Immanuel Hospital Bandung from January 2013 to December 2014 based on the prevalence, gender, age, clinical features, metastasis, and mortality percentage. The method design was a descriptive retrospective method with data retrieval and collection of patient medical records that have been diagnosed with lung cancer in Immanuel Hospital Bandung from January 2013 to December 2014 period. This study showed that lung cancer prevalence was 51 patients, the majority of patients were males compared to females with the ratio of 2.7:1, the most common age group was 61–70 years old, the most common clinical features were dyspnea and cough, the most common site of metastasis was liver, and the mortality percentage was 33.33%.Keywords: Immanuel hospital Bandung, lung cancer, patient’s description